I need help simplifying expressions:

i have 9x+2-5x-3 four

I need help simplifying expressions:

i have 9x+2-5x-3 four

Tutors, please sign in to answer this question.

If it helps at all, the reason you can re-order the terms in the problem is because you can think of subtraction as adding negative numbers:

9x + 2 - 5x - 3 = 9x + 2 + (-5x) + (-3)

Because of the commutative property of addition, we can re-order these terms in any way we like. You usually want to re-order the terms in a way that makes the problem easier, like putting like-terms next to each other:

9x + 2 + (-5x) + (-3) = 9x + (-5x) + 2 + (-3)

From here we can group and combine like-terms:

9x + (-5x) + 2 + (-3) = (9x - 5x) + (2 - 3) = (4x) + (-1) = 4x - 1

Knowing how to properly re-order, group, and combine terms without changing the value of the expression is important to being able to solve this sort of problem efficiently. As with anything, practice makes perfect. After doing enough simplification, it'll become second nature and you'll be using simplification in other problems without thinking about it. When you've mastered your simplification much of math becomes easier, so keep practicing! =)

9x + 2 - 5x - 3 = 9x + 2 + (-5x) + (-3)

Because of the commutative property of addition, we can re-order these terms in any way we like. You usually want to re-order the terms in a way that makes the problem easier, like putting like-terms next to each other:

9x + 2 + (-5x) + (-3) = 9x + (-5x) + 2 + (-3)

From here we can group and combine like-terms:

9x + (-5x) + 2 + (-3) = (9x - 5x) + (2 - 3) = (4x) + (-1) = 4x - 1

Knowing how to properly re-order, group, and combine terms without changing the value of the expression is important to being able to solve this sort of problem efficiently. As with anything, practice makes perfect. After doing enough simplification, it'll become second nature and you'll be using simplification in other problems without thinking about it. When you've mastered your simplification much of math becomes easier, so keep practicing! =)

Combine the like terms ...

= 9x + 2 - 5x - 3

= 9x - 5x + 2 - 3

= 4x - 1